Causative Constructions in Belitong Language - I Nyoman Pasek Darmawan; Nurachman Hanafi; Lalu Muhaimi; Untung Waluyo; Kamaludin Yusra (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study analyses and describes the phenomenon of valency-raising in Belitong language through causativization strategy. This study is conducted under the qualitative descriptive study alongside Relational Grammar (RG) theory. The process of collecting data is done in the forms of elicitation technique, interview with the native speakers, and documentation of the previous studies as well as some additional works of literature. The data were analysed carefully by following six procedural steps of the technique of analysing qualitative data proposed by Creswell (2009). The results of this study showed that: (1) Belitong accounts for two types of causative construction: morphological and analytic causative; (2) morphological causatives are signalled out by certain markers like suffixes -an, -ek, -kan or zero marker -Ø; and (3) analytic causatives are indicated by the insertion of the productive causative additional verbs such as muat, isak, gara-gara, nyuro, base, melasa, karne, and muji. To sum up, the revaluation principles for morphological causatives constructions are designated as 1–2 (causative); OBL–2, 2–Cho (applicative-causative) for intransitive clause; 1–2, 2–Cho (monotransitive); and 1–2, 2–Cho, OBL–OBL (transitive). Conversely, analytic causatives account for a relational structure such as 1–2.